Quality Improvement Initiative to Reduce Time from Regional Anesthesia Placement to Delivery for Cesarean Delivery - La Rosa, Mauricio; Omere, Chasey; Webb, Camille; Goldman, Brett; Laird, Rachel; Munn, Mary; Saade, George R.; Olson Koutrouvelis, Gayle (American Journal of Perinatology, 2020)
Objective Our objective was to evaluate the impact of a quality improvement (QI) initiative on the regional anesthesia placement-to-infant delivery time during cesarean delivery (CD).Study Design We performed a quality improvement trial. Before June 18, 2018, the preoperative protocol was as follows: the anesthesiologist administered regional anesthesia in the operating room then the nurse placed the Foley's catheter, clipped pubic hair, precleaned the abdomen, and abdominal preparation. On June 18, 2018, the protocol changed and all the preoperative preparation (Foley's clip and preclean) were performed prior to the arrival in the operating room. The records of patients who underwent scheduled or nonemergency CD between May 1 and July 15, 2018, were reviewed. Our primary outcome was time between the placements of regional anesthesia to infant delivery at the time of CD. Bivariate and multivariable analyses were performed.Results A total of 194 patients were included, 124 before and 70 after the process change. The change in process leads to a significant reduction in anesthesia-to-delivery time, even after adjusting for number of prior CD and body mass index (BMI). Other times were also significantly impacted by the change.Conclusion Our QI initiative significantly decreased the time from anesthesia placement to delivery of the fetus. Performing preoperative preparation activities, such as Foley's placement and shaving, after regional anesthesia for CD, increase the risk of fetal exposure to maternal hypotension. We evaluated the impact of a QI initiative on regional anesthesia placement to infant delivery time during CD.
Keywords: Cesarean; quality improvement; regional anesthesia; delivery; time